Is poverty in Myanmar on the rise? Poverty predictions from Google mobility data - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
The severe economic impacts of COVID-19 on Myanmar’s economy have been accentuated by the recent political instability. In this note, we present the most recent evidence on changes in Google consumer mobility data, since these are leading indicators of changes in household income, and use a previous econometric model linking mobility indices to survey-based household poverty to predict what may be happening to poverty in Myanmar in 2021.